Aristotle's Nicomachean Ethics : Reader's Guide - Warne, Christopher (London Continuum, 2006)
Offers an account of Aristotle's "Nicomachean Ethics" - a key philosophical work. This book sets Aristotle's work in context, introduces the major themes and provides a detailed discussion of the key sections and passages of the text. It goes on to explore some of the areas of thought that the "Nicomachean Ethics" has impacted upon
Include Notes, Bibliography and Index
Keywords: Nicomachean ethics (Aristotle) -- Aristotle -- Ethics